Розвиток українсько-грецьких культурних контактів: тижні (дні) грецької культури у м. Одеса - Терентьєва, Н. (Інститут історії України НАН України, 2009)
Розглянута діяльність Одеської філії «Фонду грецької культури» (ФГК), що сприяє ознайомленню населення України з досягненнями грецької культури та сприяє відродженню й розвитку культурної самобутності греків України. The article provides a detailed analysis of the initiative of the “Fund of the Greek Culture” NGO as an effective instrument aimed at growing public awareness in terms of Greek cultural heritage. The primary objective is to promote popularization of Greek culture, its rich and diverse cultural heritage. The publication also examines different forms of FGC functioning (Odessa branch).